Ethical standards for distribution of Covid-19 relief aid - Vincent Stephen Kabuk (Center for Humanities and Innovation Studies, 2020)
The surge of the deadly coronavirus (COVID-19) brought both physical and mental anguish to humanity. It has claimed lives within a short period more than any phenomenon the world had ever witnessed throughout history. The pandemic has exerted direct consequences on the social and economic lives of the globe. These make the whole world live in continuous trepidation. As the entire human race is hopeful of eradicating the menace, humanitarian measures are put in place to promote people's welfare and happiness by providing material and logistic assistance to those in need. Indeed, there has been a tremendous response to the global call to ameliorate the pandemic's general human suffering. Nonetheless, the distribution patterns of the relief aid in countries like Nigeria has raised a lot of concerns, where a more significant chunk of the target group has not benefited from the relief aid considering the considerable amount claimed to have been shared by the government. As a result of this, the paper considers certain egalitarian principles that will serve as regularizing parameters in the distribution of COVID-19 relief aid.